Prevalence of skin changes in diabetes mellitus and its correlation with internal diseases: A single center observational study - Kaushik Ghosh; KapilDev Das; Susmita Ghosh; Sisir Chakraborty; Sanat Kumar Jatua; Ambarish Bhattacharya; Manas Ghosh (Wolters Kluwer Medknow Publications, 2015)
Background and Aim: This single-center observational cross-sectional study has been done in an attempt to find out the prevalence of various skin manifestations in diabetes patients (DM) and their correlation with diabetes control and complications. Materials and Methods: Skin manifestations present over 12 months among those attend diabetes clinic were included in the study. Apart from demographic data and type, patients were also screened for micro vascular complications and control of diabetes over last 3 months. Results and Discussion: Sixty (n = 60) diabetes patisents (Type 1 DM, 9 patients and Type 2 DM 51 patients) have been found to have various skin lesions. Thirty-one (51.67%) patients presented with infectious conditions, vascular complications were present in 21 (35%) and dermatomes belonging to the miscellaneous group were present in 50 (83.33%) patients. Pyoderma, diabetic dermopathy, and pruritus without skin lesions were found to be most common manifestations in infective, vascular and miscellaneous group, respectively. Higher level of HB1 AC was found in patient with diabetic bulla (10.5 ± 0), scleredema (9.75 ± 0.77), lichen planus (9.3 ± 1.6), and acanthosis nigricans (9.15 ± 0.89). Patients with psoriasis and vitiligo had statistically significant lower level of glycosylated hemoglobin (P =< 0.001 and 0.03, respectively). However, no association of any kind of skin manifestation with DM with other microangiopathic complications was found in this study.